The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0030624
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia pestis Lineages in Mongolia

Abstract: BackgroundWhole genome sequencing allowed the development of a number of high resolution sequence based typing tools for Yersinia (Y.) pestis. The application of these methods on isolates from most known foci worldwide and in particular from China and the Former Soviet Union has dramatically improved our understanding of the population structure of this species. In the current view, Y. pestis including the non or moderate human pathogen Y. pestis subspecies microtus emerged from Yersinia pseudotuberculosis abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 32 publications
5
41
0
3
Order By: Relevance
“…By comparison, in an active CRISPR-Cas system such as that of Streptococcus thermophilus, 77 % of spacers have viral protospacer matches . Spacers of bacterial origin have been observed in other bacteria, for example in Yersinia pestis (Riehm et al, 2012). It is also interesting to note the imbalance of spacer maintenance where identical spacers are present in more than one serovar.…”
Section: Discussionmentioning
confidence: 89%
“…By comparison, in an active CRISPR-Cas system such as that of Streptococcus thermophilus, 77 % of spacers have viral protospacer matches . Spacers of bacterial origin have been observed in other bacteria, for example in Yersinia pestis (Riehm et al, 2012). It is also interesting to note the imbalance of spacer maintenance where identical spacers are present in more than one serovar.…”
Section: Discussionmentioning
confidence: 89%
“…In Y. pestis, CRISPR typing was able to identify the origin of the ancestor strains that caused the black plague (36). Whereas it had been assumed that the black plague originated from Mongolia, CRISPR typing suggested that this region harbored a different, less virulent Yersinia species (Yersinia microtus clade) (37). A separate study had linked geographical sources to outbreaks of Y. pestis isolates based on sequence variation within the CRISPR array (38).…”
Section: Figmentioning
confidence: 99%
“…Given the temporal organization of spacers, sequencing of CRISPR arrays has been a tremendously useful tool in investigating and constructing phylogenetic relationships between different bacterial lineages, specifically, in Yersinia species, Erwinia amylovora, E. coli, and Salmonella enterica and, most recently, in the periodontal pathogen Porphyromonas gingivalis (23,(31)(32)(33)(34)(35)(36)(37)(38). CRISPR analysis from metagenomic data can also be used to identify both the presence of and relationship between viruses and hosts within complex and diverse ecological niches (26,30,(39)(40)(41).…”
Section: What Are Crisprs?mentioning
confidence: 99%